#1**+1 **

answer=sqrt85

Feel free to ask how I got this answer, and tell me if this is correct or not:)

whymenotsmart May 19, 2020

#2**+1 **

Just to expalin

The quadratic formula is

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

So we have

\(x = {7 \pm \sqrt{-7^2-4*(-9)} \over 2} = {7 \pm \sqrt{49-36} \over 2} = {7 \pm \sqrt{13} \over 2}\)

That's then +/- sqrt(13), so the difference is (7+sqrt(13))/2 - (7-sqrt(13))/2 =

(7 - 7 + sqrt(13) - ( - sqrt(13))/2 = 2(sqrt(13))/2 = sqrt(13)

So I believe the answer is sqrt(13)

So I don't understand where the sqrt(85) came from.

hugomimihu May 19, 2020